The media, informal learning and ageism in Ibadan, Nigeria (2014)
In recent decades, public perceptions of old people have been shifting towards negativity. Stereotypes of ageing may shape behaviours towards the aged, and may complicate the social, nutritional, psychological and health conditions of the elderly. The perception and attitude of people toward the aged cannot be separated from the informal learning outcomes that flowed through or permeated their interactional episodes as well as their encounters and specific events. From the premise of cultivation theory, it is assumed that the stereotypes surrounding beliefs and attitudes about the aged are cultivated from informal, everyday learning through the media. Thus, study examines ageism among young people and the extent to which these beliefs match the ways the elderly are portrayed in the media. Using Nollywood movies as an example of media form to which young people in Nigeria are exposed, the study tests the hypothesis that convergence exists in the extent of ageist beliefs and representations in the media among students of tertiary institution in Ibadan. The result shows that all the dimensions of ageism measured through the modified ageing quiz are represented or enacted in Nollywood movies. While respondents have ageist perceptions of their own, the representations of older persons they encounter in movies are not so different. One effective way to address ageism is to employ the channel through which these stereotypes were constructed in the first place. Through informal learning arrangements, advocacy may be kick-started by exposing the aged and other members of the society to accurate information on what ageing entails.